Aprosodia and prosoplegia with right frontal neurodegeneration. Issue 5 (3rd September 2019) - Bateman, James R.; Filley, Christopher M.; Ross, Elliott D.; Bettcher, Brianne M.; Hubbard, H. Isabel; Babiak, Miranda; Pressman, Peter S.
ABSTRACT: Affective prosody and facial expression are essential components of human communication. Aprosodic syndromes are associated with focal right cerebral lesions that impair the affective-prosodic aspects of language, but are rarely identified because affective prosody is not routinely assessed by clinicians. Inability to produce emotional faces (affective prosoplegia) is a related and important aspect of affective communication has overlapping neuroanatomic substrates with affective prosody. We describe a patient with progressive aprosodia and prosoplegia who had right greater than left perisylvian and temporal atrophy with an anterior predominance. We discuss the importance of assessing affective prosody and facial expression to arrive at an accurate clinical diagnosis.